Evaluating the Effectiveness of Allergenspecific Immunotherapy in Children with Pollinosis Using Doppler Study of Sublingual Salivary Glands - M. V. Ryazanov; L. S. Namazova-Baranova; M. V. Gorshkov; I. A. Krotov; V. Yu. Yaltikov (Педиатрическая фармакология)
Background: The allergen-specific immunotherapy (ASIT) is the only method of etiopathogenetic treatment of allergic diseases. Noninvasive method of ASIT is the most popular for children population. Given the features of salivary glands’ anatomy, authors suggested the possibility of using ultrasound diagnosis in salivary glands’ study to determine the effectiveness forecast of ASIT.Objective: Our aim was to evaluate a possibility of using Doppler study of sublingual salivary glands as an accessible method of evaluation of future ASIT efficacy.Methods. A prospective randomized comparative controlled study was held. All children underwent an ultrasound procedure of sublingual salivary glands; children with pollinosis underwent it twice, with an assessment of intraparenchymal hemodynamics before and after ASIT.Results. 160 children with pollinosis in remission period aged 5–17 and 40 children aged 5–17 without burdened allergic history were included in the study. When comparing bloodstream parameters in patients after ASIT with sublingual, parenteral and combined method with positive effect, it is established that the values of all indexes increased in sublingual glands. In children treated with sublingual method these values even exceeded the values of comparison group. In patients receiving ASIT sublingually, parenterally or with combined method without a positive effect in dynamics, all the sublingual salivary glands Doppler study parameters were comparable to those of comparison group. Endonasal method has not shown any significant results either befor or after the ASIT course.Conclusion. The sublingual salivary glands Doppler study can be used as an additional efficacy criterion of future ASIT, which will be carried out sublingually, parenterally or with combination of those two methods.